Human papillomavirus vaccine series completion in boys before and after recommendation for routine immunization. Issue 6 (7th February 2017) - Ackerson, Bradley; Hechter, Rulin; Sidell, Margo; Sy, Lina S.; Slezak, Jeffrey; Chao, Chun; Patel, Nilesh; Tseng, Hung-Fu; Jacobsen, Steven
Highlights: HPV vaccination plays an important role in reducing HPV-associated cancers. Male 4vHPV series completion was low (24.3%) despite ACIP routine use recommendation. Completion was greater in younger boys (11–12 years) than older boys (13–17 years). Early initiation and identification of a primary care provider may improve 4vHPV series completion. Abstract: Background: Although the incidence of HPV-attributable cancers in males is rapidly increasing, HPV vaccine uptake in males remains poor. While quadrivalent human papillomavirus vaccine (4vHPV) series initiation in males increased following the Advisory Committee Immunization Practices (ACIP) male routine use recommendation, its impact on 4vHPV series completion in males at ACIP-recommended intervals has not been evaluated in large male cohorts. We examined trends and correlates of 4vHPV completion since licensure in males in a large cohort of insured boys before and after the ACIP routine use recommendation. Methods: We grouped data from electronic medical records of males aged 9–17 years from Kaiser Permanente Southern California health plan who initiated 4vHPV into 3 cohorts by 4vHPV initiation date: licensure and ACIP permissive use: 2009–2010; addition of anal cancer indication: 2010–2011; ACIP routine use: 2011–2013. We estimated adjusted hazard ratios (AHRs) between patient and provider characteristics and vaccination using Marginal Cox proportional hazards models. Results: Of 80, 800 boys initiating 4vHPV, 24.3% completed the series within 12 months with minimal differences across cohorts. Completion decreased with increasing age at initiation (13–17 vs. 11–12 year olds: AHR = 0.85; 95% confidence interval [CI] = 0.80, 0.89) and was greater among patients with a primary care provider (AHR = 1.28, 95%CI = 1.17, 1.41), influenza vaccine recipients (AHR = 1.50, 95% CI = 1.43, 1.57), and Asian/Pacific Islanders (AHR = 1.07, 95% CI = 1.00, 1.15), and lower among non-Hispanic Blacks (AHR = 0.72, 95% CI = 0.65, 0.80) and Hispanics (AHR = 0.86, 95% CI = 0.81, 0.90) compared to non-Hispanic Whites. Conclusions: Despite the ACIP routine use recommendation in males, 4vHPV series completion remained low. 4vHPV initiation at 11–12 years and identification of a provider responsible for the adolescents' health care may increase 4vHPV series completion. Given the rapidly increasing incidence of HPV-related cancers in males, it is important to identify measures to increase HPV vaccine series completion, particularly among non-Hispanic Black and Hispanic males.